Modifikasi Penampung Slurry pada Bioreaktor Portabel Penghasil Biogas - I Putu Karisma Yogi; I Putu Surya Wirawan; Gusti Ngurah Apriadi Aviantara (Jurnal BETA (Biosistem dan Teknik Pertanian), 2024)
Using PVC tarpaulin as a slurry container in portable bioreactors has a high potential for leakage. This research aims to determine the ability of a 200 - liter High - Density Polyethylene (HDPE) plastic tube to contain slurry in a portable bioreactor with an airtight (anaerobic) biogas fermentation process. The equipment design is carried out structurally (includes calculating the volume of the reactor tube, volume of the gas c hamber, and volume of the slurry chamber) and functionally (includes making the inlet channel, residue outlet channel, and gas channel). The parameters tested include temperature, pH, and biogas pressure. The research results showed that fermentation of a mixture of pig manure slurry and water for 25 days produced a biogas volume of 0.0487824 m3, the resulting temperature was 20 o C - 29.9 o C (mesophilic), and the pH value of the slurry during the fermentation process was 6.3. HDPE plastic tubes can be used as s lurry containers because they can carry out the fermentation process in an airtight (anaerobic) manner